Incorporating Nursing Diagnosis and King’s Theory in the O.R. Documentation - Gill, Janet; Hopwood-Jones, Laurel; Tyndall, Judi; Gregoroff, Susan; LeBlanc, Patricia; Lovett, Cathy; Raso, Luba; Ross, Anne (Operating Room Nurses Association of Canada Journal, 1995)
The Operating Rooms at the Hamilton Civic Hospitals share the same documentation format. The need to revise the documentation to incorporate the standards from the Operating Room Nurses Association of Canada was recognized. The Hamilton Civic Hospitals, Department of Nursing, adopted Imogene King’s Conceptual Framework as the model for nursing practice. The ﬂowsheet developed for the Operating Rooms incorporated both King’s Theory and Nursing Diagnosis.